Determine density contribution of basement rock by modeling of 3D gravity inversion - Thanh, Đỗ Đức; Dũng, Nguyễn Kim (Vietnam Journal of Earth Sciences, 2013)
In this paper, method based on the combine of anomaly "peeled layer" calculating with three - dimensional gravity inversion is researched in oder to determine the density contribution of basement rock. By this method, depth to bottom of sedimentary layers is defined by another geophysical methods. Gravity field component of upon sedimentary layers with suggestion that the variation of sedimentary basin’s density contrast is approximated to a exponential function are calculated at each observed point. Residual field component separated from the total observed anomaly after removing this field components as well as regional field component is considered as the field component, that reflects inhomogenous of density of basement rock. It is used to determine density contribution of basement rock based on the nonlinear optimization technique of the Marquardt algorithm. Algorithm is programed in Matlab code to atempt on three dimensional mathematical models.The results received by experimentally calculating in respect of precision, convergence as well as feasibility computer time show the ability of application of the method.